Implementasi Diversifikasi Penanganan Anak Sebagai Pelaku Tindak Pidana Kekerasan - Muhammad Isya, Ibrahim (Proceedings Series on Social Sciences & Humanities, 2024)
This This research discusses the implementation of the juvenile justice system in Indonesia with a focus on the application of the concept of diversion as an effort to protect children in conflict with the law. Children, as assets for the nation's future, often face various problems, including delinquency and criminal behavior which is worrying. Along with the flow of globalization, the development of information technology has had both positive and negative impacts on children, who often imitate the inappropriate behavior they see in the media. This research uses empirical juridical methods by collecting facts from human behavior both through interviews and observations. direct. The research results show that the application of diversion is effective in providing protection and rehabilitation to children in conflict with the law, as well as preventing them from repeating criminal acts in the future. Apart from that, this research also highlights the importance of synergy between aspects of structure, substance and legal culture in implementing diversion. Thus, diversion in the juvenile criminal justice system in Indonesia provides an opportunity to safeguard the best interests of children and prevent them from the negative stigma of the formal justice process. Law Number 11 of 2012 concerning the Juvenile Criminal Justice System is the main legal basis for implementing diversion, which is expected to increase legal protection for children and optimize their rehabilitation.